Trademark Rights Dispute (Geprek Bensu With I Am Geprek & Singapore Company With Hadi Darsono) - Bonaraja Purba; Inda Serfina Tarigan; Noel Ramot Denvico Tamba; Nova Novita Pardede (Indonesian Journal of Advanced Research, 2023)
Legal protection of Intellectual Property Rights (IPR) is very important to encourage technological progress. By providing legal protection to writers, technology creators and artists, IPR can inspire people to create more. The research method used is descriptive qualitative research method. This research uses data sources that are written records, namely cases that occur and can be accessed freely on news media pages and so on. The results of this study explain that the settlement of intellectual property rights disputes over the culinary business brand Geprek Bensu with I Am Geprek Bensu based on the Commercial District Court has been decided by decision Number 57/Pdt. Sus. Brand/2019/PN Niaga Jkt Pst. The Supreme Court decided to reject Ruben Onsu's lawsuit and granted the reconception of PT Ayam Geprek Sujono." The judge stated that PT Ayam Geprek Sujono was the legal owner and first user of the name "Bensu" in the I Am Geprek Bensu trademark. Because Ruben Onsu had bad faith and had similarities resembling the brand of PT Ayam Geprek Sujono, the registration certificate with the six names of Geprek Bensu was cancelled. And in the "Lotto" brand dispute, the sanctions or penalties given to the first defendant must be pay the case fines that have been written in the lawsuit.